Islamic Religious Education Learning Management At Gema Pelita Vocational School - Adah Aliyah; Fiqih Amrullah; Uus Ruswandi; Bambang Samsul Arifin (At-Tarbiyat, 2023)
The purpose of this study was to determine the Management (Design, Implementation, and Evaluation) of Learning Learning at SMK Gema Pelita. This research uses a qualitative approach while the method used is descriptive. The data collection techniques were carried out through observation, interviews, and documentation. The research location is focused on SMK Gema Pelita. The research subjects were the clerics, ustad and santri. Data analysis is carried out by selecting and sorting out the answers to the data obtained then collected to be analyzed and conclusions drawn. The data analysis used is using data triangulation. The data validity test uses the stages of credibility, transferability, dependability, and confirmability. This study found that in Islamic Religious Education (PAI) education at SMK Gema Pelita, there is an emphasis on inclusive learning design, learning implementation that involves various methods and technologies, and holistic evaluation. This supports the goal of PAI education to provide a deep understanding of Islamic teachings and encourage the application of religious values in students' daily lives. Thus, the school creates a conducive learning environment that focuses on students' character development, in line with the vision of comprehensive and practical PAI education.